2022
DOI: 10.7759/cureus.26046
|View full text |Cite
|
Sign up to set email alerts
|

An Exceptionally Rare Primary Epithelioid Rhabdomyosarcomas of the Stomach: A Case Report

Abstract: Rhabdomyosarcoma (RMS) is a common soft tissue tumor in adults, but RMS's causes and risk factors are unknown. We present a case of a 62-year-old man with RMS who presented with feelings of fullness after meals and vomiting for the previous five months with anorexia and weight loss for four months. He reported feeling a rolling mass in his belly that moves from left to right. He was initially diagnosed with gastric outlet obstruction due to stomach carcinoma. During the surgical operation, we noted the gross a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Alveolar RMS (ARMS) accounts for 31% of all cases and occurs commonly in individuals aged 10-25 years, mostly in the extremities, followed by the trunk or the perineural region (4). Occurrence in the stomach is extremely rare and an early definitive diagnosis is difficult (5). The tumors are highly malignant and prone to distant lymph node metastasis (6).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alveolar RMS (ARMS) accounts for 31% of all cases and occurs commonly in individuals aged 10-25 years, mostly in the extremities, followed by the trunk or the perineural region (4). Occurrence in the stomach is extremely rare and an early definitive diagnosis is difficult (5). The tumors are highly malignant and prone to distant lymph node metastasis (6).…”
Section: Introductionmentioning
confidence: 99%
“…RMS of the stomach is extremely rare, with only four previously published cases (4-7). The reported cases have included epithelioid (4,5), pleomorphic (6) and embryonal (7) RMS of the stomach. To the best of our knowledge, the present study contains the first reported case of primary gastric ARMS.…”
Section: Introductionmentioning
confidence: 99%